Implikasi Putusan Mahkamah Konstitusi Terhadap Regulasi Production Sharing Contract - Cut Asmaul Husna TR (The Constitutional Court of the Republic of Indonesia, 2012)
After the Constitutional Court ruling has implications for regulatory 36/ PUU-X/2012 production sharing contract. Relationship between BP Migas (state) with the Business Entity or Permanent Establishment has put the state’s position and business entities or permanent establishments that manage oil and gas in an equal position. As a result, the state lost discretion to make regulations for the benefit of the people, but the state, as a representation of the people in the control of natural resources should have the discretion to make rules that benefit the overall prosperity of the people. Some of the conditions are far from optimal, Indonesian oil and gas industry is still heavily dependent on foreign domination. Associated with the conditions present in Aceh, the amount of funding for oil and gas shares, did not show a decrease in the poverty rate